2021
DOI: 10.1111/pin.13076
|View full text |Cite
|
Sign up to set email alerts
|

Maternal death analysis based on data from the nationwide registration system in Japan (2010–2018)

Abstract: The maternal mortality rate in Japan was 3.5 per 100 000 live births in 2017, similar to that reported in other developed countries. To reduce the number of maternal deaths, a Japanese nationwide registration and analysis system was implemented in 2010. Between January 2010 and April 2018, 367 maternal deaths were reported. Among them, by reviewing 80 autopsy records, the direct obstetric causes of death were identified in 52 women. The major causes of deaths were amniotic fluid embolism and acute pulmonary th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These findings strongly support the notion that an influx of amniotic fluid materials in the maternal circulation induces maternal inflammatory and anaphylactoid reactions in AFE. However, there is little pathological evidence to suggest haemostatic alteration in AFE, except for the above description 19–21 . The present study provides pathological evidence that amniotic fluid material that enters the uterine venous circulation induces platelet aggregation and activates the coagulation cascade, resulting in thrombus formation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These findings strongly support the notion that an influx of amniotic fluid materials in the maternal circulation induces maternal inflammatory and anaphylactoid reactions in AFE. However, there is little pathological evidence to suggest haemostatic alteration in AFE, except for the above description 19–21 . The present study provides pathological evidence that amniotic fluid material that enters the uterine venous circulation induces platelet aggregation and activates the coagulation cascade, resulting in thrombus formation.…”
Section: Discussionmentioning
confidence: 55%
“…However, there is little pathological evidence to suggest haemostatic alteration in AFE, except for the above description. [19][20][21] The present study provides pathological evidence that amniotic fluid material that enters the uterine venous circulation induces platelet aggregation and activates the coagulation cascade, resulting in thrombus formation. However, the uterine venous thrombi were not observed in half of the AFE cases.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…5,6 Surprisingly, a recent report demonstrated that the prevalence of self-harm death between 2005 and 2014 in Tokyo, Japan (8.7/100 000 women) was much higher than that reported previously (2.8/100 000 women in 2014 on average in Japan). 5 In addition, this is higher than the prevalence of obstetric-related maternal deaths, including stroke, postpartum hemorrhage, amniotic fluid embolism, and peripartum thromboembolism (3.5/100 000 women in Japan in 2017), 5,7,8 and is also higher than that in other countries (1.3-5.9/100 000 women in Europe and the United States). 5,9,10 As perinatal mental health care is of growing importance, the identification of women at high risk of PPD in advance is necessary to provide timely therapeutic intervention and social support.…”
Section: Introductionmentioning
confidence: 95%
“…Up to 10% of pregnant individuals will experience some form of mental condition, some of which can have a lethal outcome . As maternal death due to critical obstetric hemorrhage has decreased worldwide, possibly through improvements in medical practice, equipment, and blood supply systems, the maternal death rate by suicide has increased. Suicidal death is currently considered to account for 5% to 20% of maternal mortality in developed countries, but the exact risks of peripartum suicide attempts remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%